Evaluation of beta integrals of Ramanujan type and integral representations for bilateral hypergeometric series - Cohl, Howard S.; Volkmer, Hans (The Ramanujan journal, 2025)
In this paper we evaluate integrals of products of gamma functions of Ramanujan type in terms of bilateral hypergeometric series. In cases where the bilateral hypergeometric series are summable, then we evaluate these integral as beta integrals. In addition, we obtain integral representations for bilateral hypergeometric series.